A novel SOX18 mutation uncovered in Jordanian patient with hypotrichosis–lymphedema–telangiectasia syndrome by Whole Exome Sequencing. Issue 1 (February 2016) - Bastaki, Fatma; Mohamed, Madiha; Nair, Pratibha; Saif, Fatima; Tawfiq, Nafisa; Al-Ali, Mahmoud Taleb; Brandau, Oliver; Hamzeh, Abdul Rezzak
Abstract: The SOX18 gene encodes a transcription factor that plays a notable role in certain developmental contexts such as lymphangiogenesis, hair follicle development and vasculogenesis. SOX18 mutations are linked to recessive and dominant hypotrichosis–lymphedema–telangiectasia syndrome (HLTS). In this study we report on a novel heterozygous mutation in SOX18 in a Jordanian patient suffering from HLTS that was revealed by Whole Exome Sequencing. In this case, a frameshift caused by 14-nucleotide duplication in SOX18 appeared de novo resulting in a premature translational stop at the N-terminal region of the central trans-activation domain. Here we present the clinical manifestations of the above mentioned molecular lesion in the light of what is known from published SOX18 mutations. Highlights: A novel SOX18 variant; (c.492_505dup), was uncovered in a child suffering from HLTS. This is the first report of HLTS in Arabs; parents are a non-consanguineous Jordanian couple. The affected is heterozygous for the variant which appeared de novo in him. The mutation probably leads to C-terminally truncated protein.